Pengaruh Lingkungan Kerja dan Budaya Organisasi terhadap Kinerja Karyawan - Tiara Dwi Yanti; Tita Safira; Tiara Puspita Dewi Hidayat (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This research aims to understand the impact of workplace factors or organizational values on workforce productivity through a qualitative approach. The study is not focused on a single company, but rather explores data from various sources through in-depth interviews and observations of relevant participants within the research context. This approach was chosen to obtain a comprehensive picture of how these two factors can influence employee motivation, productivity, and responsibility in diverse work contexts. The research findings indicate that a supportive and enabling work environment, both physically and socially, plays a key role in fostering work enthusiasm. Meanwhile, an inclusive and adaptive organizational culture tends to encourage positive and productive work behaviors. These findings emphasize the importance of management attention to environmental and cultural aspects in efforts to continuously improve employee performance.